Chiral Compounds: Photoinvertible Chiral Liquid Crystal that Affords Helicity‐Controlled Aromatic Conjugated Polymers (Advanced Optical Materials 20/2020). Issue 20 (19th October 2020) - Yoshida, Satoru; Morikawa, Santa; Ueda, Kenta; Hidaka, Masatomo; Kaneko, Kosuke; Kaneko, Kimiyoshi; Hanasaki, Tomonori; Akagi, Kazuo
Abstract : Novel chiral compounds bearing a photoresponsive moiety linked with an axially chiral moiety are synthesized by Kazuo Akagi and co‐workers (see article number 2000936 ) and used as chiral dopants to prepare photoinvertible chiral nematic liquid crystals (N*‐LCs). Electrochemical polymerizations of 3, 4‐ethylenedioxythiophene are achieved in the N*‐LC to afford photochemically helicity‐controlled helical conjugated polymers.